Life cycle surplus and life cycle deficit of immigrants versus natives - Tofoska Apostolova, Persida Cica (Economic and business review, 2022)
Recently, immigration and its socio-economic aspects have been in the centre of the European Union leaders’ agenda. In this paper, we apply the National Transfer Accounts (NTA) methodology to calculate the complete set of NTA results for immigrants and natives in five EU countries. We find that due to the lower labour income, which cannot be offset by the lower consumption, immigrants experience a shorter independence period and a much lower aggregate life cycle surplus than natives. The identified cross country differences between immigrants and natives could be used as a proxy of the achieved level of integration of immigrants.
Keywords: demografija; demography; EU; imigracije; immigrations